Drinking Motives and Willingness to Drink Alcohol in Peer Drinking Contexts. (February 2017) - Anderson, Kristen G.; Garcia, Tracey A.; Dash, Genevieve F.
Drinking motives are important proximal predictors of alcohol consumption in adolescents and emerging adults (EAs). Despite the importance of peer context on alcohol use decision-making, research on drinking motives is commonly divorced from the contexts where such decisions are made. Behavioral willingness (BW), or openness to engaging in a given behavior, is a contextually dependent aspect of nondeliberative decision-making for youth. As BW and drinking motives are proximal predictors of alcohol use, it was hypothesized that they would interact in the prediction of later drinking. Eighty-seven EAs reported their BW in simulated drinking contexts, drinking motives, and alcohol consumption upon entering college as well as drinking patterns 8 months later. Context-specific BW potentiated coping motives' impact on increased alcohol consumption and potentially hazardous drinking at the end of participants' first year. These findings support the importance of BW and context in understanding motivation's role in drinking behavior for EAs.